Comparison of 99mTc-DMSA, 99mTc-DTPA and 99mTc-MAG3 Renal Scintigraphy in the Calculation of Relative Renal Function - Demir, Fadime; Demir, Mustafa (Galenos Yayincilik, 2020)
Objective: The aim of this study was to compare Tc-(9)(9m) dimercaptosuccinic acid (Tc-99m-DMSA) renal cortical scintigraphy and Tc-(9)(9m) diethylene triamine pentaacetic acid (Tc-99m-DTPA) and Tc-(9)(9m) mercaptoacetyltriglycine (Tc-99m-MAG3) dynamic renal scintigraphy in the evaluation of relative renal function (RRF). Materials and Methods: Forty seven patients with renal cortical scintigraphy (with Tc-99m-DMSA) and dynamic renal scintigraphy (with Tc-99m-DTPA or Tc-99m-MAG3) were included in this retrospective study. RRF obtained from Tc-99m-DMSA, Tc-99m-DTPA and Tc-99m-MAG3 scintigraphies, clinical and demographic data were statistically analyzed. Results: There was a high correlation between Tc-99m-DMSA renal cortical scintigraphy and dynamic renal scintigraphy (Tc-99m-DTPA or Tc-99m-MAG3) in terms of RRF evaluation (r=0.981, p<0.001 and r=0.918, p=<0.001, respectively). While the Bland Altman plot showed an average difference of 3.30 between RRFs measured by Tc-99m-DMSA and by Tc-99m-DTPA, the difference between that with Tc-99m-DMSA and Tc-99m-MAG3 was 0.08. Conclusion: In conclusion, this study showed a high level of compliance between Tc-99m-DMSA renal scintigraphy and dynamic renal scintigraphy (Tc-99m or Tc-99m-MAG3) in the evaluation of RRF. Time loss, radiation exposed to the patients and economic losses are minimized with the use of a single method suitable for the purpose.
Keywords: Relative renal function; Tc-99m DMSA renal cortical scintigraphy; Dynamic renal scintigraphy